1985
DOI: 10.1111/j.1744-7348.1985.tb01578.x
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of leaf growth in sugar beet.

Abstract: SUMMARY The increase of leaf area index (L) was examined in a series of sugar‐beet crops grown on different sites (Broom's Barn, Suffolk and Trefloyne, Dyfed) or with different husbandry treatments (sowing dates and nitrogen rates) between 1978 and 1982. The development of L could be described as a function of thermal time using three parameters; DE, which was essentially an estimate of the thermal time required for crop establishment, and rHL and DL, the thermal rate and duration, respectively, of the increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…In the field trials, leaf regrowth was observed after drought stress was relieved. This ability of sugar beet has already been described by Owen & Watson (1956) and Milford et al (1985). The primary explanation is of a botanical nature: the sugar beet crop is cultivated during its vegetative phase only, i.e.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In the field trials, leaf regrowth was observed after drought stress was relieved. This ability of sugar beet has already been described by Owen & Watson (1956) and Milford et al (1985). The primary explanation is of a botanical nature: the sugar beet crop is cultivated during its vegetative phase only, i.e.…”
Section: Discussionsupporting
confidence: 71%
“…no ontogenic signal prevents leaves from growing during this period (Perata et al 2004). Milford et al (1985) showed, on a series of distinct sugar-beet crops grown during five consecutive seasons, that a linear relationship could be fitted between leaf number and thermal time until 2000°C after sowing, with no plateau, suggesting that it could increase at the same rate for longer. This result was confirmed in the present work by the last measurements made in December in the Avignon trial, illustrating sugar beet's ability to produce new leaves throughout its life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of days (DNo) was calculated from planting to harvest date. Thermal time (growing degree-days, GDD) was calculated by summing the daily values of mean temperatures minus the threshold value of 3°C (Milford et al, 1985), from the planting to the harvest date. Weather conditions in the years 2016 and 2017 differed especially in the precipitation, average temperatures and insolation (Table 4, Supplementary Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Previous works by Milford et al [51] suggested that ca. 750 • C·d is necessary for beet to form a closed canopy, while Malnou, Jaggard and Sparkes [42] reported that 900 • C·d and 100 kg N·ha −1 were required for the crop to reach 85% canopy.…”
Section: Field Trialsmentioning
confidence: 99%